Fenomen rozmowy w dramacie - Jarząbek, Dorota (Przestrzenie Teorii, 2007)
The subject of this article is the departure of drama in the direction of conversation - a linguistic fact of great existential and social importance. Although conversation itself seems to be nondramatic, in fact it revolutionises the concept of time, space, action, forming separate genres and trends in drama. The author distinguishes three models of conversational drama (in which a conversation became either a subject or a building material of the whole work of drama): the theatre of amorous conversation (A. de Musset, C. Norwid), theatre of intellectual confrontation (conversation in the drama of ideas in G.B. Shaw's style), theatre discussing its own status and functions (an improvisation/impromptu genres). Thus, the drama based on the autonomy of conversation is not a 20th century invention, although its old, intellectual and rhetoric models have been replaced by modern categories: of body and voice.